2010
DOI: 10.1093/ndt/gfq550
|View full text |Cite
|
Sign up to set email alerts
|

Role of thiamine status and genetic variability in transketolase and other pentose phosphate cycle enzymes in the progression of diabetic nephropathy

Abstract: The results support the role of 'functional' thiamine deficiency in the development of hyperglycaemia-related pathology. Limited intracellular availability of active TKT co-factor seems to be a dominant abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 14 publications
0
29
0
1
Order By: Relevance
“…However, a further study has shown increased plasma thiamine levels with progressive renal impairment and proteinuria suggesting decreased renal clearance of thiamine (21)…”
Section: Mechanismsmentioning
confidence: 99%
“…However, a further study has shown increased plasma thiamine levels with progressive renal impairment and proteinuria suggesting decreased renal clearance of thiamine (21)…”
Section: Mechanismsmentioning
confidence: 99%
“…7 Thiamine is the co-factor of transketolase in pentose phosphate pathway and in high doses it increases the activity of this enzyme leading to disposal of excess cytosolic glucose. 16 The products of pentose phosphate pathway are non-harmful to cell. On the other hand the decreased flux through hexosamine and protein kinase C pathway decreases glycosylation of glucose transporters.…”
Section: Discussionmentioning
confidence: 99%
“…TKT activity was measured indirectly as previously described [26] using kinetic NADPH-dependent method utilizing triose phosphate isomerase (180 U ml −1 ) and glycerol-3-phosphate dehydrogenase (7.3 U ml −1 ). Reaction rates were expressed as picomoles of substrate converted per second under specified conditions related to milligrams of haemoglobin in erythrocyte lysate.…”
Section: Tkt Activity and Thiamine Effectmentioning
confidence: 99%